Axial compression tests of grouted connections in jacket and monopile offshore wind turbine structures. (1st October 2019) - Chen, Tao; Wang, Xian; Gu, XiangLin; Zhao, Qi; Yuan, GuoKai; Liu, JinChao
Highlights: Seven cylindrical grouted connection specimens with shear keys were designed and tested. Two specimens represented jacket structures were tested by pure compression. The other five ones represented monopile structures were axially compressed after two million bending cycles. The five monopile residual specimens had competent residual axial compression capacities. The FE models for specimens could reflected the failure mode, maximum capacities and the strain distributions. Abstract: Grouted connections (GCs) are widely used in offshore wind turbines to transfer multiple loads from their upper structures to their foundations. Among these loads, axial loads and bending moments dominate in most structural forms. As reported in this paper, a total of seven GC specimens were tested under ultimate axial compression. Two specimens, A-Pre and A-Pos, respectively representing the pre-installed and post-installed pile construction technique in jacket foundations, were directly tested under axial loading. Meanwhile, the other five specimens (RA-1 to RA-5), representing the GCs in monopile foundations, were compressed after 2 million cycles of fatigue bending moments (except RA-5). All seven specimens failed because their steel tubes buckled. However, in Specimen A-Pos, before the steel tube buckled, the grout material broke and slippage occurred, while the axial capacity increased even after the slippage. For the five monopile GC specimens, the failure mode of steel tube buckling indicated that the GCs still had competent axial capacities even after being subjected to fatigue bending moments. It is possible that fabrication quality, rather than fatigue loading histories, dominated the residual capacity in these tests. Moreover, three-dimensional (3D) finite element (FE) models of these GCs were also constructed. The simulation of ultimate axial capacities, failure modes, and stress distributions were basically consistent with the experimental results.